MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN LAYANAN MUTU PENDIDIKAN DI PKBM QIYYA SANTOSA KABUPATEN BANDUNG - Yuningsih, Yuyun; Fitriani, Seni; Sumarni, Sri; Ratnawulan, Teti; Suwandari, Lilis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the management of facilities and infrastructure in improving the quality of educational services at PKBM Qiyya Santosa, Bandung Regency. The research background is based on the importance of facilities and infrastructure as one of the national education standards that play a strategic role in supporting the learning process, particularly in non-formal education units that often face resource limitations. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, presentation, and verification techniques. The findings indicate that the management of facilities and infrastructure at PKBM Qiyya Santosa has been implemented through the application of POAC management functions (Planning, Organizing, Actuating, Controlling). Planning is carried out in a participatory manner based on the actual needs of learners and budget constraints. Organizing includes clear task distribution among managers, tutors, and education staff, as well as the implementation of standard operating procedures for facility use. The execution of procurement is conducted gradually through government assistance, self-help, and community support, while the utilization of facilities is optimized through tutors’ creativity. Supervision is carried out regularly through internal monitoring and evaluation to ensure sustainability. Although challenges such as limited budgets and learning spaces remain, adaptive and participatory management of facilities and infrastructure has proven to contribute positively to improving the quality of educational services at PKBM Qiyya Santosa.